2021
DOI: 10.1093/ckj/sfab243
|View full text |Cite
|
Sign up to set email alerts
|

How common is hyperkalaemia? A systematic review and meta-analysis of the prevalence and incidence of hyperkalaemia reported in observational studies

Abstract: Background The prevalence and incidence of hyperkalaemia, a potassium abnormality which can potentially have life-threatening consequences, is unclear. Objective To provide the most comprehensive overview of the epidemiology of hyperkalaemia to date both within the general population, across different continents, in different healthcare settings and within pre-specified sub-groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 15 publications
1
26
0
5
Order By: Relevance
“…However, pulmonary oedema was described in a patient with kidney failure and hypertensive heart disease following 100 mL of 50% dextrose administered as a bolus [ 21 ]. Since hyperkalaemia frequently occurs in patients with kidney failure [ 1 ], decisions regarding the rate and volume of dextrose utilised should include the assessment of the patient’s volume and cardiac status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pulmonary oedema was described in a patient with kidney failure and hypertensive heart disease following 100 mL of 50% dextrose administered as a bolus [ 21 ]. Since hyperkalaemia frequently occurs in patients with kidney failure [ 1 ], decisions regarding the rate and volume of dextrose utilised should include the assessment of the patient’s volume and cardiac status.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalaemia is a very common electrolyte disorder encountered in hospitalized patients [ 1 ] and, if left untreated, may result in life-threatening cardiac arrhythmias and death. The emergency treatment of hyperkalaemia includes shifting potassium into cells using intravenous insulin, with dextrose added before, with or after insulin administration to prevent hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review reported a prevalence of 8·6% and an incidence rate of 5·1 cases per 100 person-years for hospitalised patients when hyperkalaemia was defined as a [K] of more than or equal to 5·5 mmol/L. 1 However, these frequencies included patients receiving kidney replacement therapy. No studies from the African continent reported on incidence, and only three reported on the prevalence of hyperkalaemia, 13 , 15 , 16 ([K] ≥ 5·5 mmol/L), which was high at 36·7%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent, comprehensive systematic review reported an overall, global prevalence of 8·6% and an incidence of 5·1 cases per 100 person-years for hyperkalaemia, defined as a [K] ≥ 5·5 mmol/L, in hospitalised patients. 1 Few studies were identified from the African continent and none of the studies from Africa reported on the incidence of hyperkalaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Eskişehir Osmangazi Üniversitesi Tıp Fakültesi İç Hastalıkları, Romatoloji Bilim Dalı'nda Ocak 2010-Şubat 2020 yılları arasında SLE tanısı ile takip edilen hastalar SLE ICD kodu kullanılarak belirlendi. Hiperkalemi, potasyum düzeyi ≥5.5 mEq/L olarak kabul edildi (8). SLE için 1997 Amerikan Romatoloji Derneği (ACR) sınıflandırma kriterlerini (9)…”
Section: Hasta Seçimiunclassified